Built Environment Analysis for Road Traffic Crash Hotspots in Kigali, Rwanda - Wang, Daphne; Krebs, Elizabeth; Nickenig Vissoci, Joao Ricardo; de Andrade, Luciano; Rulisa, Stephen; Staton, Catherine A. (Frontiers in Sustainable Cities, 2020)
Introduction: Road traffic injuries (RTIs) are a significant cause of morbidity and mortality in Rwanda. Investigations of the high risk areas for road traffic crashes (RTCs) are urgently needed to guide improvements in road safety. This study aims to identify RTC hotspots in Kigali, Rwanda, and to conduct a built environment analysis of these hotspots. Methods: RTC and RTC-prone locations were collected from the Kigali Traffic Police and high frequency road users, and hotspots were identified through kernel density estimation. Built environment characteristics (BEA), including road design, road safety, pedestrian safety, and traffic density, were collected for each hotspot. BEA characteristics were associated with risk of RTC using logistic regression and BEA scores were calculated using principal component analysis. Patterns of BEA were identified through exploratory cluster analysis and associated with risk for RTC using logistic regression. Results: 25 RTC hotspots were identified. High crash risk locations were less likely to have unpaved roads (21%, p = 0.049) and road narrowing (21%, p = 0.049). High crash risk locations were also more likely to have pedestrian walkways (100%, p = 0.009), factors aiding pedestrian crossing (100%, p = 0.026), and poor road surfaces (86%, p = 0.005). Cluster analysis showed that hotspots with fewer urban characteristics, including road safety features, motor vehicle density, and pedestrian safety features, have significantly decreased odds of being a high mortality risk hotspot than a hotspot with more urban characteristics (OR = 0.13, 95% CI 0.02–0.79). Conclusions: RTC hotspots were in the city center with high motor vehicle density but did have road and pedestrian safety features, suggesting that speeding is a major cause of RTCs. Effective traffic calming measures and enforcement of road safety laws may reduce the burden of road traffic injuries in Kigali but additional analyses are recommended.